The Evaluation of Financial Profitability Determinants Post Initial Public Offerring Case: PT Goto Gojek Tokopedia TBK - Mayora Andrea Utomo; Jagat Prirayani; Erman Sumirat (Cv. Syntax Corporation Indonesia, 2026)
The COVID-19 pandemic and tightening global macroeconomic conditions have put significant pressure on digital platform companies following the initial public offering (IPO), including PT GoTo Gojek Tokopedia Tbk. Despite recording high transaction and user growth, the company still faces challenges in achieving sustainable financial profitability. This study aims to analyze the determinants of GoTo's financial profitability in the post-IPO period by reviewing the role of internal organizational factors and external market factors. The research uses an explanatory quantitative approach with quarterly time-series data for the period 2018–2025. Profitability is measured through return on assets (ROA) and return on equity (ROE). The analysis was carried out using time-series regression with the Augmented Dickey–Fuller stationarity test and Newey–West robust estimation. The results show that internal organizational factors, especially operational efficiency reflected in the EBITDA margin, have a significant effect on ROA. In contrast, external factors such as the level of competition, business confidence, inflation, and economic growth did not show a significant influence on ROE in the short term. These findings confirm that GoTo's post-IPO profitability is determined more by the quality of internal execution than external market conditions. This research provides strategic implications for digital platform companies in managing the transition from growth-oriented to financial sustainability.